2019
DOI: 10.1089/ars.2018.7678
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of Nicotinamide Adenine Dinucleotide Phosphate Oxidase 2 in Skeletal Muscle Redox Signaling and Metabolism

Abstract: Significance: Skeletal muscle is a crucial tissue to whole-body locomotion and metabolic health. Reactive oxygen species (ROS) have emerged as intracellular messengers participating in both physiological and pathological adaptations in skeletal muscle. A complex interplay between ROS-producing enzymes and antioxidant networks exists in different subcellular compartments of mature skeletal muscle. Recent evidence suggests that nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOXs) are a major sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 410 publications
1
34
0
Order By: Relevance
“…Nox2 is a membrane oxidoreductase that produces ROS in response to skeletal muscle contractions [ 26 ] and stretch [ 27 ]. Extracellular ROS appear to communicate with neighboring myocytes, thus regulating contractile function [ 28 , 29 ], glucose uptake [ 30 , 31 ], pre-conditioning elevation of stress-protective proteins [ 32 ], metabolism [ 33 ], and gene expression [ 34 ]. However, the assembly of the Nox2 complex dramatically rises with Duchenne muscular dystrophy [ 35 ] and Type II diabetes [ 36 ], contributing to pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Nox2 is a membrane oxidoreductase that produces ROS in response to skeletal muscle contractions [ 26 ] and stretch [ 27 ]. Extracellular ROS appear to communicate with neighboring myocytes, thus regulating contractile function [ 28 , 29 ], glucose uptake [ 30 , 31 ], pre-conditioning elevation of stress-protective proteins [ 32 ], metabolism [ 33 ], and gene expression [ 34 ]. However, the assembly of the Nox2 complex dramatically rises with Duchenne muscular dystrophy [ 35 ] and Type II diabetes [ 36 ], contributing to pathology.…”
Section: Discussionmentioning
confidence: 99%
“…3 indicate that oxidation of the mitochondrial isoform (Prx3) occurred with contractile activity in addition to the cytosolic-located isoforms (Prx1 and 2). Recent studies have implicated NADPH oxidase 2 as the major source of contraction-induced ROS generation [ 46 , 50 , 51 ], but older [ 6 ] and some longer duration studies [ 51 ], suggested mitochondria might also be an important source of ROS during muscle contractions. While the source of the ROS that induced oxidation of Prx3 in this model is unclear, the data in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle has several sources of ROS, but mitochondria [ 14 ], NADPH oxidase enzymes (NOX/DUOX) [ 15 ], and xanthine oxidase (XO) [ 16 ] seem to be the three most relevant during exercise. While O 2 •− are generated by mitochondria and XO as a secondary sub-product of oxidative phosphorylation and purine metabolism, respectively, NAPDH oxidase enzymes are exclusively dedicated to generating superoxide and H 2 O 2 [ 17 , 18 ] ( Figure 1 ).…”
Section: Main Sources Of Ros In Skeletal Muscle During Contractionmentioning
confidence: 99%
“…Activation of the NOX2-p22phox complex requires the translocation of cytosolic factors such as p47phox, p67phox, and p40phox to the membrane. Phosphorylation of p47phox induces a change in its conformation that enables it to bind p22phox, thus promoting the interaction of the other cytosolic factors with NOX2 [ 18 ]. Additionally, p22phox is a functional binding partner of NOX4, but its activity seems to be mainly dependent on its expression level, as well as the partial oxygen pressure [ 17 , 29 , 35 ].…”
Section: Main Sources Of Ros In Skeletal Muscle During Contractionmentioning
confidence: 99%